Plant community distribution and diversity, and threats to vegetation of the Kromme River peat basins, Eastern Cape Province, South Africa - Nsor, Collins Ayine (Rhodes University, Faculty of Science, Department of Environmental Science, 2008)
This study examined the current plant diversity status and the impact of drivers of change on the peat basins of the Kromme River peatland. It was conducted at six sites over sixty one years in the Eastern Cape Province of South Africa. I reviewed the rapid habitat and biodiversity loss of wetlands globally and discussed the distribution of wetlands and specifically peatlands in South Africa. Plant species diversity was assessed using Modified- Whittaker plots. The influence of environmental variables on floristic composition and distribution was investigated using ordination techniques (DCA and CCA). Land use dynamics were assessed by applying GIS techniques on orthorectified aerial images. Six different peat basins were subjectively classified into good, medium and poor condition peat basins. The good condition peat basin (Krugersland) was the most diverse in plant species (4.1 Shannon-Weiner's index) (p> 0.20; F = 11.04; df = 2), with the highest mean number of plant species (32.5 ± 3.4). This was followed by the medium condition class (Kammiesbos) (26.5 ± 9.0) and poor condition class (Companjesdrift) (22.5 ± 8.9). On average, species composition was not evenly distributed across the peat basins (p> 0.21; F = 0.94; df = 2), since 77.8% of the Shannon-Weiner evenness index obtained were less than one. However, there were variations in plant species richness across six peat basins as confirmed by Oneway ANOVA test (p= 0.0008, F = 1241.6, df = 4). Key environmental variables that influenced plant species distribution and structure were erosion and grazing intensity, potassium, phosphorus, soil pH and calcium. Total species variance accounted for in the first two axes for ground cover and plant height were 40.7% and 56.4% respectively. Alien species (e.g. Acacia mearnsii and Conyza scabrida) were common in degraded peat basins, whereas good condition peat basins supported indigenous species (e.g., Cyperus denudatus, Chrysanthemoides monolifera and Digitaria eriantha). Analysis of aerial images revealed a general progressive decrease in the peatland area between 1942 and 1969 in the good (Krugersland) and poor (Companjesdrift) condition class, with a marginal increase from 1969 to 2003. Peatland area in the good and poor condition class decreased by 5.3% and 8.3% respectively between 1942 and 1969, with a marginal increase of 1.5% and 4.1% respectively from 1969 to 2003. Annual net rate of change in peatland area over the 61 year period was -0.32% (good condition class) and - 0.79% (poor condition class). Transformed lands were impacted by drivers of change such as alien invasives, agricultural activities, erosion and sediment transport. The area under alien invasives increased by 50% between 1942 and 2003, with an annual net rate of change of +0.82 (good condition class) and +1.63% (poor condition class).
Keywords: Kromme River (Eastern Cape, -- South Africa); Peatland ecology -- South Africa -- Eastern Cape; Plant diversity conservation -- South Africa -- Eastern Cape; Peatland plants -- South Africa -- Eastern Cape; Peatlands -- South Africa -- Eastern Cape; Biodiversity -- South Africa -- Eastern Cape; Wetland conservation -- South Africa -- Eastern Cape; Ecosystem management -- South Africa -- Eastern Cape